Birth rate analysis in the state of Paraná from 2011 to 2021: trends in fertility rates, maternal age, and the influence of education on delivery type (Research, Society and Development, 2023)
This retrospective study aimed to understand the trends and factors influencing birth rates in the state of Paraná. Data from the Ministry of Health from 2011 to 2021 were analyzed, revealing a decline in birth rates over time, in line with the national trend. A significant finding was the significant increase in the average maternal age, highlighting the need to prepare the healthcare system to cater to older pregnant women and consider the impacts on both mothers and children. While the majority of births were delivered by cesarean section, there was no significant increase in cesarean deliveries among mothers with higher levels of education, suggesting that education does not necessarily determine the type of delivery. Additionally, there was an increase in vaginal births among more educated pregnant women, partially contradicting this hypothesis. It is important to note that the analysis was solely based on data from the Ministry of Health, limiting the assessment of mothers' education level in terms of completed educational stages. However, the results provide relevant information about birth rates in Paraná, revealing the decline in fertility rates, the increase in average maternal age, and the predominance of cesarean sections as the most common type of delivery. These findings have significant implications for public policies and healthcare interventions aimed at supporting pregnant women, facilitating appropriate family planning, and promoting best obstetric practices. Understanding these aspects is crucial for gaining a deeper understanding of the demographic landscape and reproductive dynamics in Paraná.